Efektivitas Pendidikan Kesehatan Dengan Media Video Edukasi Dalam Meningkatkan Pengetahuan dan Perubahan Sikap Bullying Siswa SMP Negeri 5 Kota Kupang - Keni Novanto Mira Higa; Ribka Limbu; Tadeus A. L. Regaletha (Yayasan Literasi Sains Indonesia, 2024)
Health education is important in supporting health programs. Health education can be done using video media. Video media is a strategy that can be used to increase knowledge and change attitudes about bullying. Based on a survey conducted, bullying often occurs at SMP Negeri 5 Kupang City. The aim of this research is to determine the effectiveness of health education using video media in increasing knowledge and changing bullying attitudes of students at SMP Negeri 5 Kupang City. This type of research is quantitative with a pre-experimental design, one group pretest and posttest. Sampling used proportional random sampling technique with a sample of 73 respondents. The research instrument used a questionnaire and video media. The analysis used in the research is univariate to determine the distribution and frequency description of the variables and bivariate analysis using the paired-sample t-test. The research results showed that after education was carried out using educational video media, there were differences in knowledge and changes in students' attitudes regarding bullying, with a significance value of ρ = 0.00 or a smaller value of α = 0.05. It is recommended that video media can be used as information about bullying in junior high school students